Revision of the leafhopper tribe Krisnini (Hemiptera: Cicadellidae: Iassinae) of the Indian subcontinent - Viraktamath, C. A. (Zootaxa, 2006)
Two genera of the leafhopper tribe Krisnini, Gessius Distant & Krisna Kirkaldy, that occur in the Indian subcontinent, are redefined and a key to separate them is provided. Gessius verticalis Distant is redescribed. Eleven species of Krisna, including eight new species [namely: K. bakeri sp. nov. (Nepal: Katmandu, India: Uttaranchal), K. burmanica (Myanmar), K. delta sp. nov. (Nepal), K. megha sp. nov. (India: Assam, Meghalaya), K. raja sp. nov. (India: Kerala), K. varia sp. nov. (India: Karnataka, Kerala, Maharashtra, Tamil Nadu), K. veni (India: West Bengal), and K. walayari sp. nov. (India: Kerala)] are described and illustrated. A key to identify these species is also provided.